Perception of extreme musical dissonance in cochlear implant users using a novel listening task - Gilbert, Melanie L.; Limb, Charles J.; Kim, Eric K.; Deroche, Mickael L. D.; Lewis, Rebecca M. (Frontiers in Audiology and Otology, 2025)
HypothesisWe hypothesized that a novel harmonic consonance-dissonance music perception task would reveal a monotonic relationship between harmonic consonance and pleasantness ratings by NH listeners. Additionally, we hypothesized that CI recipients will be able to distinguish between the most consonant and most dissonant music samples, although with more variability and less contrast between each condition than the NH cohort and with lower overall ratings of sound quality. Finally, we hypothesized that listeners with extensive music training would show more pronounced differences in pleasantness ratings across the four tiers of consonance to dissonance.BackgroundHarmonic consonance and dissonance are key components of music's perceived quality and pleasantness. However, tools to evaluate these musical aspects, especially for CI users, are scarce, leading to significant knowledge gaps. This study aimed to refine previous methods by emphasizing the variability and typically lower scores among CI users, aligning these findings more closely with their reported experiences and existing literature.MethodsA total of 34 participants (21 NH and 13 CI) completed the 30-min music task, which involved listening to music samples with various levels of harmonic consonance-dissonance ranging from complete consonance to extreme dissonance, and then rating the samples on a 5-point “pleasantness” scale. Participants also provided details about their musical training and listening habits.ResultsNH listeners consistently rated Tier D (extreme dissonance) as the least pleasant and confirmed the expected monotonic relationship between consonance and pleasantness. CI recipients, while unable to distinguish between adjacent tiers (A and B, B and C, C and D), did show a significant difference in ratings between Tiers A and D, and between B and D. Their ratings for Tiers A–C were centered around “slightly pleasant,” reflecting lower overall pleasantness scores compared to NH participants. Musical training was correlated with greater differentiation in pleasantness ratings in both NH and CI groups, suggesting that formal training enhances sensitivity to harmonic dissonance.ConclusionsThe findings suggest that CI users perceive extreme manipulations of dissonance, and propose the potential for a shorter, refined version of this test for clinical use or further research. This task could aid in optimizing CI configurations for enhanced music enjoyment.